Global magnetodisk disturbances and energetic particle injections at Jupiter. Issue 6 (13th June 2014) - Louarn, Philippe; Paranicas, Christopher P.; Kurth, William S.
Abstract: Measurements made by the Galileo Energetic Particles Detector and the plasma wave/radio instrument are analyzed to establish relationships between dynamic processes observed independently in the distant and the inner Jovian disk (at 80–120 Jovian radii ( RJ ) and 10–25 RJ, respectively). It is first shown that global magnetospheric disturbances identified from the radio emissions (the "energetic events" are well correlated with reconnection/reconfiguration events observed at the outer edge of the disk. Then, considering all Galileo perijoves, it is also demonstrated that the energetic events occurring as Galileo was at less than ~25 RJ are systematically associated with new injections of energetic particles seen from ~10 to 25 RJ . This demonstrates that major disturbances commonly affect the whole magnetodisk, from 10 to 80–120 RJ . Overall, their phenomenology involves simultaneous auroral activation, formation of new sources of radio emission (narrow‐band kilometric radiation) and particle injections in the Io torus, magnetic reconfigurations, and radial flow bursts in the distant disk, over time scale of a few hours. Key Points: Link between particle injections and large‐scale disk disturbances at Jupiter Global‐scale dynamics of Jovian magnetodisk Combined analysis of EPD and PWS Galileo data